Teachers' Perspectives on the Independence of Children Aged 5–6 Years Under Grandparental Care - Nimatuzahroh; Pranoto, Yuli Kurniawati Sugiyo; Mulawarman (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
The increasing prevalence of children being raised by their grandparents due to parental migration, economic hardship, or family separation has raised concerns regarding its impact on children's autonomy and psychosocial development. This study examines teachers' perspectives on the independence of children aged 5–6 years under grandparental care. Employing a quantitative descriptive design, the research assessed 119 children in Cibinong, Bogor, using an adapted version of Iijima’s (1985) independence diagnostic test. Four indicators of independence were measured: spontaneity, self-control, autonomy, and self-assertion. Descriptive statistical analysis revealed that spontaneity (M = 57.76, SD = 7.78) and autonomy (M = 31.30, SD = 4.51) were categorized as high, self-control (M = 18.73, SD = 3.17) as moderate, and self-assertion (M = 15.53, SD = 2.68) as low. These findings suggest that while children under grandparental care exhibit independence in daily activities, they struggle with self-assertion, which is crucial for effective social interactions and decision-making. The study highlights the need for targeted interventions, such as role-playing exercises and structured decision-making tasks, to strengthen self-assertion skills. Additionally, parenting workshops for grandparents could help bridge gaps in independence development. Limitations include reliance on teacher-reported data; thus, future research should incorporate observational methods and longitudinal studies to explore the long-term impact of grandparental caregiving on children's independence. Understanding the implications of grandparental care is essential for designing early childhood education strategies and caregiving policies that support holistic child development.